The municipals archives in Extremadura at the end of the 18th century through the Royal Court - Solano Macías, Carmen (2023)
At the beginning of 1791, the Real Audiencia of Extremadura carried out a questionnaire in all the villages of the province, which were then grouped into nine territorial demarcations called “partidos”. This questionnaire was answered by the authorities of Extremadura villages, and was supplemented with the reports made by the visitor of the Audiencia responsible for each demarcation. The survey addresses, among other topics, the situation and characteristics of the public archives. Taking as basis the information collected in the answer sheets of the different villages and in the visitors' reports, we have developed an information system that has allowed us to analyse the situation of these archives within the geographic-temporal environment in which the questionnaire was carried out. Thus, we discover the ambiguity that existed in the concept of archive, their existence in the villages of Extremadura, their physical location, who managed them, the types of documents that were kept in them and the problems they presented. All this shows the general panorama of the public archives in Extremadura at the end of the Modern Age.